Soot primary particle sizing in a n-heptane doped methane/air laminar coflow diffusion flame by planar two-color TiRe-LII and TEM image analysis. (15th April 2020) - Patiño, F.; Cruz, J.J.; Verdugo, I.; Morán, J.; Consalvi, J.L.; Liu, F.; Du, X.; Fuentes, A.
Abstract: Soot primary particle size distribution along the centerline of a laminar coflow methane/air diffusion flame doped with vaporized n-heptane at atmospheric pressure was studied using the planar two-color time-resolved laser-induced incandescence (TiRe-LII) technique and analysis of transmission electron microscope images. An improved thermophoretic probe sampling procedure was used to collect samples of soot particles. The LII signals captured at two wavelength bands in the visible are used to determine the soot effective temperature by two-color pyrometry. The methodology was first validated against the literature data obtained in a laminar coflow ethylene/air diffusion flame. The same methodology is then applied to the n-heptane doped methane flame along the flame centerline. The Sauter and geometric mean diameters of soot primary particles were obtained. Good agreement is found between the soot primary particle size distributions obtained by the two techniques.